Controlled Synthesis, Characterization, and Flow Properties of Ethylene–Diene Copolymers. Issue 3 (30th January 2019) - Das, Chinmay; Elguweri, Muhiddin; Jiang, Peijun; Kang, Shuhui; Kelchtermans, Mauritz; McLeish, Tom C. B.; Parkinson, Matthew; Read, Daniel J.; Redlich, Michael P.; Shirodkar, Pradeep P.; Soulages, Johannes M.
Abstract: The flow response of branched entangled resins is dominated by the branching topology of the constituent molecules, a property that is not directly accessible using experimental analytical tools for industrially relevant complex resins. In this paper, the controlled terpolymerization of ethylene, 1, 9‐decadiene, and either hexene or octene in a continuous stirred tank reactor with a metallocene catalyst, is reported. The synthesized samples are characterized extensively with various analytical tools and their rheological properties are measured with small amplitude oscillatory shear and start‐up uniaxial extension experiments. A model is developed for the polymerization process with the mass balance during synthesis providing strong constraints on the rate constants. In silico ensembles of molecules, generated via Monte Carlo sampling, are used to reproduce the experimental results. The computer model allows us to infer the detailed branching structure of the molecules and to predict the optimum range of reactor conditions for this synthesis. Abstract : Integrated computer modeling of synthesis and characterization reveals the detailed branching structures in a set of ethylene–diene copolymers . Controlled synthesis is achieved for different concentrations of diene and another comonomer. Combining multiple experiments and modeling enhances the understanding about the synthesis and allows to theoretically determine the appropriate reactor conditions for polymers with given desired flow properties.